On the impact of self-assessment on EFL learners' receptive skills performance - Shahrakipour, Hassan (Penerbit Universiti Kebangsaan Malaysia, 2014)
It is believed that self-assessment can influence learners' learning achievement (Dearing, 1997; Falchikov, 1997; Stefani, 1998; Taras, 2001, 2002). It can also influence language learners' writing and speaking performance (Alibakhshi & Abbaszadeh, 2012). However, the impact of self-assessment on EFL learners' listening and writing skills has not been widely studied yet. This study was an attempt to see whether self-assessment can influence EFL learners' receptive skills. It also tried to observe whether it has the same effect on intermediate and beginner language learners. The sample for the study consult 120 Iranian language learners who were selected convenience sampling. They were grouped as beginner and intermediate language learners. The experimental groups received a treatment on self-assessment and they self assessed their outcomes. All groups received a posttest. The data were analyzed through ACNOVA test. The results showed that self assessment significantly improved EFL learners' receptive skills. However, the effect value of self-assessment on listening skill was less than reading skill. Also, self-assessment effect value on beginner groups was less in comparison with intermediate groups.